2012
DOI: 10.1038/leu.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variation contributes significantly to the risk of childhood B-cell precursor acute lymphoblastic leukemia

Abstract: Recent genome-wide association studies (GWAS) have provided the first unambiguous evidence that common genetic variation influences the risk of childhood B-cell precursor acute lymphoblastic leukemia (BCP-ALL), identifying risk single-nucleotide polymorphisms (SNPs) localizing to 7p12.2, 9p21.3, 10q21.2 and 14q11.2. The testing of SNPs individually for an association in GWA studies necessitates the imposition of a very stringent P-value to address the issue of multiple testing. While this reduces false positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
0
29
1
Order By: Relevance
“…23 Nonetheless, the range of the posterior on PVE nicely spans the estimates provided by the other methods equally to both sides, proving the ability of the PVE method to quantify uncertainty in multivariate problems by assessing the full joint posterior distribution of the model parameters compared Heritability estimates on Hodgkin's lymphoma H Thomsen et al with the current simplistic 'one SNP at a time' testing paradigm, 34,35 because analyzing all SNPs simultaneously will detect more of the genetic variation because of the identification of multiple causal variants. 36 In contrast to the results of Enciso-Mora et al, 37 our estimates of the variance are almost constant across the different numbers of SNPs and do not decline after a more stringent exclusion of missing genotypes. This is in agreement with the results by Yang et al 19 and Lee et al 38 Thus, our QC has been stringent enough beforehand.…”
Section: Discussioncontrasting
confidence: 55%
“…23 Nonetheless, the range of the posterior on PVE nicely spans the estimates provided by the other methods equally to both sides, proving the ability of the PVE method to quantify uncertainty in multivariate problems by assessing the full joint posterior distribution of the model parameters compared Heritability estimates on Hodgkin's lymphoma H Thomsen et al with the current simplistic 'one SNP at a time' testing paradigm, 34,35 because analyzing all SNPs simultaneously will detect more of the genetic variation because of the identification of multiple causal variants. 36 In contrast to the results of Enciso-Mora et al, 37 our estimates of the variance are almost constant across the different numbers of SNPs and do not decline after a more stringent exclusion of missing genotypes. This is in agreement with the results by Yang et al 19 and Lee et al 38 Thus, our QC has been stringent enough beforehand.…”
Section: Discussioncontrasting
confidence: 55%
“…Although GWAS are widely recognized as rigorous in their approach to identifying disease loci [101], the P value requirements for defining a significant association, in return, increases the probability of missing a true association as recently demonstrated specifically in childhood leukemia. Using previously derived methods [102,103] applied to an analysis of nearly 250,000 SNP genotypes from the UK GWAS [79], Enciso-Mora et al [6] estimated that about 24 % of the total variation in childhood B-cell precursor ALL risk is accounted for by common genetic variation, and the previously identified loci (IKZF1, ARID5B, CEBPE, and CDKN2A) explain only 8 % of this total. This study provides evidence for a polygenic mechanism of susceptibility and rationale for continued investigation of additional susceptibility loci that were likely missed by previous GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…Undetected associations due to insufficient sample sizes, which pertain to both genome-wide and candidate gene studies, is a central issue underscored by both the EncisoMora et al report [6] and previous reviews [5,104]. Power calculations have shown that even the largest GWAS conducted to date (907 cases and 2,398 controls) had limited ability to detect variants conferring relative risks of 1.4 or below and/or those with allele frequencies of \0.10 [6,104].…”
Section: Areas Of Ongoing and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute lymphoblastic leukemia (ALL), the most common childhood malignancy, has a significant genetic basis for susceptibility (1)(2)(3)(4). As well as contributing to the risk of childhood ALL, inherited genetic variation appears to predispose to specific ALL subtypes and response to chemotherapeutic intervention (2).…”
Section: Introductionmentioning
confidence: 99%